Frontispiece: Heteroarene‐tethered Functionalized Alkyne Metamorphosis. Issue 4 (18th January 2021) - Bag, Debojyoti; Sawant, Sanghapal D.
Abstract : The use of heteroarene‐tethered functionalized alkynes in a wide range of synthetic methodologies and total syntheses of natural products is thoroughly reviewed. Synthetic transformations involving the heteroarene‐tethered functionalized alkynes with scope, challenges, limitations, mechanism, their application in the total synthesis of natural products and future perceptions are surveyed. For more details see the Review by S. D. Sawant et al. on page 1165 ff.